2017
DOI: 10.1111/vsu.12632
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leak pressures for single‐layer simple continuous suture pattern for cystotomy closure using barbed and monofilament suture material in an ex vivo canine model*

Abstract: This study showed no difference in initial or maximum leak pressure between cystotomy closures with barbed or non-barbed suture under ex vivo conditions. This indicates barbed suture may be appropriate for cystotomy closure but in vivo studies are needed to support this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 29 publications
6
30
3
Order By: Relevance
“…In support of our hypothesis, we found that there was no difference in initial leakage pressures between barbed and nonbarbed bladder closures, confirming that the use of barbed suture in an open cystotomy model is as effective as its smooth counterpart. Our findings are consistent with the findings of other studies evaluating the use of barbed suture for diaphragmatic herniorrhapy, 8 gastrotomy and enterotomy closure, 9 skin closure, 7 and canine and equine cystorrhaphy models, 10,11 showing equivalence when compared to conventional smooth suture.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In support of our hypothesis, we found that there was no difference in initial leakage pressures between barbed and nonbarbed bladder closures, confirming that the use of barbed suture in an open cystotomy model is as effective as its smooth counterpart. Our findings are consistent with the findings of other studies evaluating the use of barbed suture for diaphragmatic herniorrhapy, 8 gastrotomy and enterotomy closure, 9 skin closure, 7 and canine and equine cystorrhaphy models, 10,11 showing equivalence when compared to conventional smooth suture.…”
Section: Discussionsupporting
confidence: 91%
“…In the barbed group, the majority of the specimens leaked at the preconstructed loop at the beginning of the suture line, whereas in the nonbarbed group the majority of the specimens leaked at the knot. The locations of leakage in this study agree with those of an ex vivo canine cystorrhaphy model using barbed (V‐Loc) suture material . The cause of the observed results likely relate to the fact that there is a length of the suture material devoid of barbs adjacent to the preconstructed end loop, representing a point of uneven tension distribution during filling prior to barb occurrence at a distance of 14 mm from the preconstructed end loop .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations